Total correction of type I truncus arteriosus in a 6-month-old infant. Issue 12 (December 1975) - Singh, A; de Leval, M; Stark, J
Abstract : A successful correction of type I truncus arteriosus using a 12 mm 'dacron' conduit containing a porcine aortic valve (Hancock) between the right ventricle and the pulmonary artery in a 6-month-old infant is reported. The rationale for the treatment of truncus arteriosus in infancy is discussed.